Efficient and Selective Biosynthesis of a Precursor-Directed FK506 Analogue: Paving the Way for Click Chemistry - Goranovič, Dušan; Jenko, Branko; Ramšak, Barbara; Podgoršek Berke, Ajda; Bedrač, Leon; Horvat, Jaka; Šala, Martin; Makuc, Damjan; Carriche, Guilhermina M.; Silva, Luana; Lopez Krol, Aleksandra; Pšeničnik, Alen; et al. (Journal of natural products (Washington, D.C.), 2025)
The medically important immunosuppressant FK506 is a structurally complex macrolactone biosynthesized by a combined polyketide synthase and a nonribosomal peptide synthetase enzyme complex. Its acyltransferase domain 4 (AT4) selects an unusual extender unit, resulting in an allyl moiety on carbon 21 of the macrolactone backbone. Based on the AT4 domain, chemobiosynthetic processes have been developed that enable the introduction of diverse moieties at the carbon 21 position. However, the novel moieties that were introduced into the polyketide backbone are chemically inert. Reported here is a novel and efficient chemobiosynthetic approach that ensures high titer of an FK506 analogue containing a propargyl moiety. The novel FK506 analogue displays lower immunosuppression activity than FK506 with significantly reduced cytotoxicity. More importantly, the propargyl moiety contains a terminal alkyl group, which makes click chemistry reactions possible; this approach may potentially be translated to other medically important drugs of polyketide origin.